Australian battalion commanders in the Second World War - Pratten, Garth 1973- (Australian army history series, 2009)
Australian Battalion Commanders in the Second World War explores, for the first time, the background, role and conduct of the commanding officers of Australian infantry battalions in World War II, who, despite their vital role as the lynchpins of the battlefield, have previously received scant attention in contemporary military history.